Inductance Measurement Fixture and Mathematical Model Development to Support AC Drive System Simulation Tools - (:unkn) unknown (My University, 2017)
Variable frequency drives generate high differential-mode (DM) motor voltages due to the reflected wave phenomenon. The common-mode (CM) voltage produced by a pulse width-modulated inverter changes rapidly, which results in high peak currents to ground. For low-power variable frequency drives in long motor leads application, this can present several issues. Some of these issues include cable charging current, capacitive coupling, DC bus pump-up and failure of the power module due to high instantaneous currents that are usually undetected. In this thesis work, existing drive output filters are used to obtain a mathematical model for the inductors used in these filters. A damping matched resistor cable surge impedance is then added. This method reduces reflections of both DM and CM traveling waves, decreases peak cable charging currents and reduces CM current. Experimental and simulation results are provided to demonstrate the usefulness of the model.
Keywords: AC Drive System; Common Mode Inductor; Differential Mode Inductor; Impedance Vs. Frequency; Inductance Measurement; Saturation Characteristic